A New Dimension of Entrepreneurial Marketing and Key Challenges: A Case Study from Pakistan - Tayyab Amjad; Shamsul Huda Abdul Rani; Shiza Sa'atar (SEISENSE Journal of Management, 2020)
Purpose- Numerous studies have explored entrepreneurial marketing (EM) activities in the firms that are established for a few years, but the research exploring the EM activities and challenges, particularly during the start-up phase, is scant. To cover this wide gap, the current study explores in-depth the EM activities and EM challenges faced during the start-up phase by a graduate entrepreneur who has exposure to both marketing and entrepreneurship education and practical EM experiences. Design/Methodology- In-depth case study approach has been adopted to study an SME owned and managed successfully by a graduate entrepreneur. Findings- After rigorous data analysis, in addition to the currently known seven EM dimensions, this study has discovered a new EM dimension, i.e., ‘legitimation’. Moreover, the key EM challenges in emerging economies are also identified. Practical Implications- The results have guided future entrepreneurs regarding their investment decisions, and to the entrepreneurship education policymakers regarding pedagogical up-gradation.